2012
DOI: 10.1007/s00702-012-0787-x
|View full text |Cite
|
Sign up to set email alerts
|

Huntington’s disease from the patient, caregiver and physician’s perspectives: three sides of the same coin?

Abstract: The aim of this study was to identify determinants of functional disability, patient’s quality of life (QoL) and caregivers’ burden in Huntington’s disease (HD). Eighty HD patients participated in the study. Motor and behavioral disturbances as well as cognitive impairment were assessed using motor, behavioral and cognitive parts of the Unified Huntington Disease Rating Scale (UHDRS); Hamilton Depression Rating Scale was used to assess depression. Disability, health-related QoL and the impact of the disease on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
74
3
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(88 citation statements)
references
References 20 publications
8
74
3
3
Order By: Relevance
“…According to the results, it appears that individuals with HD, when compared to healthy individuals, they had lower scores in all domains and global scope. These data are in agreement with findings of previous studies that identified in this respect, negative influences of the disease since the beginning of its manifestations, according to family / caregivers 14,17,26 .…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…According to the results, it appears that individuals with HD, when compared to healthy individuals, they had lower scores in all domains and global scope. These data are in agreement with findings of previous studies that identified in this respect, negative influences of the disease since the beginning of its manifestations, according to family / caregivers 14,17,26 .…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, the DH impairs the mental health of individuals and may be observed suffering and emotional stress among family throughout the course of the disease 13,14 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 Depressive symptoms, 2,18,19 total functional capacity, 19,31 and cognitive performance 2,31 have been identified as the most important factors determining healthrelated quality of life (HR-QoL). Although the role of motor symptoms was secondary, UHDRS Total Motor Score was significantly correlated with the physical dimension of generic HR-QoL scales (SF-36 19 and Sickness Impact Profile…”
Section: 23mentioning
confidence: 99%